2014
DOI: 10.1002/ijc.28967
|View full text |Cite
|
Sign up to set email alerts
|

MCC inhibits beta-catenin transcriptional activity by sequestering DBC1 in the cytoplasm

Abstract: The mutated in colorectal cancer (MCC) is a multifunctional gene showing loss of expression in colorectal and liver cancers. MCC mutations can drive colon carcinogenesis in the mouse and in vitro experiments suggest that loss of MCC function promotes cancer through several important cellular pathways. In particular, the MCC protein is known to regulate beta-catenin (bcat) signaling, but the mechanism is poorly understood. Here we show that the b-cat repressor function of MCC is strongly impaired by the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…An integral part of this network, linking the main hubs HNF4A and E2F1, is MCC, which we also identified as the most potent discriminator between CAP and AECOPD by EFS. One function of MCC is the negative regulation of canonical Wnt signalling 29 , which has been observed in the airways of COPD patients 30 . The second differentiating gene as ranked by EFS is MUC1, a member of the mucin family.…”
Section: Discussionmentioning
confidence: 99%
“…An integral part of this network, linking the main hubs HNF4A and E2F1, is MCC, which we also identified as the most potent discriminator between CAP and AECOPD by EFS. One function of MCC is the negative regulation of canonical Wnt signalling 29 , which has been observed in the airways of COPD patients 30 . The second differentiating gene as ranked by EFS is MUC1, a member of the mucin family.…”
Section: Discussionmentioning
confidence: 99%
“…4,19 A recent study demonstrated that DBC1 is required for β-catenin-mediated transcription. 24 However, the detailed mechanism of how DBC1 contributes to β-catenin-mediated transcription has not been fully elucidated. Here we showed several lines of mechanistic evidence that DBC1 promotes β-catenin activity by negatively regulating SIRT1 activity (Figure 3): SIRT1-mediated deacetylation of β-catenin was inhibited by DBC1; DBC1 blocks the interaction of SIRT1 with β-catenin; and SIRT1-mediated repression of β-catenin activity was reversed by DBC1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, function-rescue assays revealed that MCC upregulation was necessary to mediate the suppressive effect of miR-4260 inhibition on cellular proliferation and migration, and resistance to 5-FU treatment in colorectal cancer cells. It has been reported that loss of MCC can lead to the activation of WNT/β-catenin signaling and thus promote cellular proliferation during colorectal tumorogenesis 11, 30, 31. Based on TargetScan bioinformatics analysis (www.targetscan.org), SMAD4 is also predicted to be a target of miR-4260.…”
Section: Discussionmentioning
confidence: 99%